Strengthening Of Education Multicultural Era MEA - - Suyahman (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study aimed to describe the strengthening of multicultural education in the era of theMEA, This research is a descriptive qualitative research in the form of library research,data collection method of documentation which examines in depth the phenomena, librarybooks, research journals, and scientific articles related to the variables studied. Dataanalysis techniques used interactive analysis technique consists of three steps: datareduction, data display and data verification. The results showed that efforts to strengthenthe multicultural education in the era of MEA can be done by keeping the essence ofmulticultural education harmonization with the essence of the MEA. That means that themulticultural education in the era of the MEA should be able to build the talents of thelearners in order to have a wide range of knowledge, experience and skills to be able tocompete in the era of the MEA while maintaining a synergism in the diversity of its ethnicdiversity, language, culture, religion and so forth. Multicultural education in the era of theMEA should also be able to provide a wide range of competencies that are multi-complexto the learners so that learners are able to take advantage of the opportunities that exist inthe era of MEA. The conclusion is that the era of multicultural education in the MEAshould be given reinforcement by providing a stock of knowledge, experience, and skillsto learners to continue to promote the harmony of their good diversity in ethnicity,language, culture or religion.Keywords: Multicultural Education and MEA Era